Estimation of the Diagnostic Value of the Shape of Trigeminal Nerves and Their Neurovascular Relationships in the Diagnosis of Trigeminal Neuralgia - A. V. Bakunovich; V. E. Sinitsyn; E. A. Mershina; Yu. A. Grigoryan (Вестник рентгенологии и радиологии)
Objective: to estimate the diagnostic value of the anatomical characteristics of the intracisternal portions of the trigeminal nerves and adjacent arteries in diagnosing classical trigeminal neuralgia (TN).Material and methods. Fast Imaging Employing Steady-state Acquisition (FIESTA) using an isotropic MRI sequence was used to analyze the anatomical characteristics of the intracisternal portions of the trigeminal nerves and adjacent arteries in 133 patients, including 86 patients aged 55±11 years with clinically and surgically verified TN and in 47 patients aged 51±16 years in the control group. The investigators measured the cross-sectional areas of the trigeminal nerves at 5 mm from the pons cerebelli, the ratio of the largest-to-smallest nerve diameters at similar points, the distance to the adjacent arteries, and that between the closest neurovascular contact (NVC) point and the pons cerebelli. Characteristic curves (CC) were constructed and reference points with the highest specificity were selected with an acceptable sensitivity level for all parameters. Positive and negative predictive values (PPV and NPV, respectively) are determined for each reference point.Results. The area under the CC was equal to 0.77 for the ratio to the diameters of the trigeminal nerves near the pons cerebelli. At a reference point of 1.89, the sensitivity/specificity (Se/Sp) ratio was 0.57/0.82 with a PPV of 0.74 and an NPV of 0.83. The area under the curve for the cross-sectional areas of the trigeminal nerves at the pons cerebelli was 0.76. The reference point with an area of 3.65 mm2 yielded a Se/Sp ratio of 0.52/0.8 with a PPV of 0.51 and an NPV of 0.91. The distance to the adjacent artery gave an area under the CC of 0.72. The Se/Sp ratio at a reference point of 1.65 mm turned out to be 0.53/0.789 at a PPV of 0.55 and an NPV of 0.92. The area under the CC for the distances between the NVC point and the pons cerebelli was 0.75. The reference point of 4.05 mm with a Se/Sp index of 0.6/0.78 was characterized by a PPV of 0.77 and an NPV of 0.94.Conclusion. All the analyzed anatomical parameters showed an acceptable diagnostic value in diagnosing TN. Certain reference values of the parameters can be used to diagnose TN with the highest acceptable specificity at the maximum NPV to reduce frequent false-positive results.